Nuclear Energy Encyclopedia 2011
DOI: 10.1002/9781118043493.ch43
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Energy Nuclear Reactions: Transmutations

Abstract: Employing concrete examples from nuclear physics it is shown that low energy nuclear reactions can and have been induced by all of the four fundamental interactions (i) (stellar) gravitational, (ii) strong, (iii) electromagnetic and (iv) weak. Differences are highlighted through the great diversity in the rates and similarity through the nature of the nuclear reactions initiated by each.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Early reports by Ohmura, Mizuno et al 1,2 were followed in the 2000s by works by Iwamura et al [3][4][5] , Celani et al 6,7 ; for a comprehensive bibliography see 8 . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports by Ohmura, Mizuno et al 1,2 were followed in the 2000s by works by Iwamura et al [3][4][5] , Celani et al 6,7 ; for a comprehensive bibliography see 8 . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Two groups have so far pursued theoretical explanations for the anomalies in fracture experiments: Cardone et al [23,37,38] based their approach on a model involving deformed spacetime; and Widom et al [39][40][41][42] have proposed that collective phenomena in condensed matter can produce energetic electrons capable of inducing nuclear disintegration. Our focus has in recent years been on the development of a theoretical model for anomalies (including elemental anomalies) in condensed matter nuclear science; here we consider the possibility of accounting for the elemental anomalies in fracture experiments in terms of the associated theoretical picture.…”
Section: Introductionmentioning
confidence: 99%
“…Most information comes from the use of deuterium because this isotope is most studied. In addition, many different nuclear reactions, including tritium formation (Storms 2007) and transmutation (Srinivasan et al 2011) are observed. Although important, these are "side issues" to heat production because they have not been found to occur at a rate sufficient to make detectable power.…”
mentioning
confidence: 99%